Nutritional Quality Evaluation of Cowpea Supplemented Food Products - Kushwaha, Archana; Verma, Astuti; Kumar, Anil (Journal of Postharvest Technology, 2014)
An experiment was conducted to develop and evaluate nutritional and sensory characteristics of food products supplemented with cowpea flour. Cowpea flour was incorporated at the levels of 20%, 40%, 60% and 80% to products made from whole wheat flour in khajure, semolina in halwa and refined wheat flour in mathri. Products prepared without cowpea flour served as control. Cowpea flour incorporation levels of 20%, 40% and 20% for khajure, mathri and halwa, respectively, was found to be significantly acceptable. Nutrient composition of acceptable cowpea supplemented food products show an increase in protein, fibre, calcium, iron , magnesium and zinc content ranging from 5.3-13.0%, 0.4 -1.5 %, 16.1-89.2%, 1.3-5.5%, 31.8-98.4% and 0.7-1.8%, respectively as compared to their control counterparts. Present study indicates that cowpea supplemented food products could be considered the best from both nutritional and sensory points of view, especially for young children.